Overcoming developing-world challenges in cochlear implantation: a South American perspective. Issue 3 (June 2018) - Bento, Ricardo F.; Bahmad, Fayez; Hippolyto, Miguel A.; Da Costa, Sady S.
Abstract : Purpose of review: Effective hearing rehabilitation with cochlear implantation is challenging in developing countries, and this review focuses on strategies for childhood profound sensorineural hearing loss care in South America. Recent findings: Most global hearing loss exists in developing countries; optimal cost-effective management strategies are essential in these environments. This review aims to assess and discuss the challenges of cochlear implantation effectiveness in South America. The authors searched electronic databases, bibliographies, and references for published and unpublished studies. Sensitivity analysis was performed to evaluate the effect of device cost, professional salaries, annual number of implants, and failure rate. Costs were obtained from experts in South America using known costs and estimations whenever necessary. Recent studies reported several challenges in unilateral or bilateral cochlear implants: cochlear implant costs, deaf education costs, increasing need for cochlear implant capacity, and training and increasing longevity. Summary: Cochlear implantation was very cost-effective in all South American countries. Despite inconsistencies in the quality of available evidence, the robustness of systematic review methods substantiates the positive findings of the included studies, demonstrating that unilateral cochlear implantation is clinically effective and likely to be cost-effective in developing countries.